Double Higgs production in vector boson fusion at NLO QCD in HEFT - Jens Braun; Pia Bredt; Gudrun Heinrich; Marius Höfer (Journal of High Energy Physics)
Abstract We present the next-to-leading order QCD corrections to Higgs boson pair production in vector boson fusion, including the leading operators in the framework of Higgs Effective Field Theory (HEFT). The corresponding calculation is based on an automated interface between the Monte Carlo event generator Whizard and the one-loop amplitude generator GoSam. The QCD corrections also include non-factorising diagrams and diagrams of Higgs-Strahlung type, thus going beyond the structure function approach. We find that some constellations of anomalous couplings, while being well within the current experimental constraints, can have a significant impact on the shape of typical observables for this process.